2021
DOI: 10.1212/wnl.0000000000012465
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Course and Features of Seizures Associated With LGI1-Antibody Encephalitis

Abstract: Objective:To determine risk factors associated with clinical relapses and development of chronic epilepsy in patients with anti-leucine-rich glioma-inactivated 1 (LGI1) IgG encephalitis.Methods:Patients with seizures related to LGI1-antibody encephalitis with ≥ 24 months of follow-up from disease onset were identified in the Mayo Clinic electronic medical record and Neuroimmunology lab records. Charts were reviewed to determine clinical factors, seizure types, imaging, treatment, occurrence of relapse, and out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(63 citation statements)
references
References 41 publications
3
48
3
Order By: Relevance
“…Our results are similar to those of a previous study with median follow‐up of 27 months in which 1.1% of patients developed epilepsy after encephalitis resolved, although that study did not clearly define epilepsy 15 . Several studies showed that 20%–37% of patients with anti‐NMDAR, anti‐LGI1, or anti‐GABA B R encephalitis developed persistent seizures or autoimmune epilepsy 13,14,30 …”
Section: Discussionsupporting
confidence: 87%
“…Our results are similar to those of a previous study with median follow‐up of 27 months in which 1.1% of patients developed epilepsy after encephalitis resolved, although that study did not clearly define epilepsy 15 . Several studies showed that 20%–37% of patients with anti‐NMDAR, anti‐LGI1, or anti‐GABA B R encephalitis developed persistent seizures or autoimmune epilepsy 13,14,30 …”
Section: Discussionsupporting
confidence: 87%
“…One explanation for the atypical memory profile could be the crowding hypothesis which describes sacrificing right hemisphere functions in favor of a relative sparing of left-hemispheric functions [12] , [13] . Another explanation might relate to the recurring right mesial temporal lobe inflammation, as indicated by an MRI in 2020.…”
Section: Discussionmentioning
confidence: 99%
“…Together with the frontotemporal focal EEG slowing since 2018, accentuated anxiety and depressive symptoms, persisting subjective cognitive and sleep problems, we cannot fully exclude a clinical relapse at this point, even though the patient has reported no seizures. Even in so-called monophasic non-paraneoplastic anti-LGI-1 encephalitis, between 35% and 40% of patients relapsed [12] , [13] . Since visual memory is dependent on the functional and structural integrity of the right temporal lobe, the described impairment can indicate a disruption of these structures [14] .…”
Section: Discussionmentioning
confidence: 99%
“…Although some LGI1 antibody-positive patients with epilepsy and especially pain respond to immunotherapies [25,64], greater residual patient-rated impairment was more prominent in CASPR2 antibody patients [63]. In one retrospective series, rituximab was used in some patients with worse outcome and, although used only as second-line therapy, 3 of 4 patients reported improvement [65]. However, the noted increase of LGI1-specific plasmablasts/plasma cells in the CSF of these patients [63] justifies anti-CD19/ CD20-specific immunotherapies.…”
Section: Experience With Rituximab In Igg-4-ndmentioning
confidence: 99%